First record of a Paranacystid mitrate from the Bokkeveld Group of South Africa - Ruta, Marcello (Bernard Price Institute for Palaeontological Research, 1997)
The Upper Eifelian paranacystid mitrate Paranacystis simoneae sp. nov. from the Waboomberg Formation (Bokkeveld Group, We stern Cape Province, South Africa) is described and a revised diagnosis of the Family Paranacystidae is presented. Paranacystis simoneae differs from Paranacystis petrii, the type species of the genus, in possessing a remarkably well-developed right subcentral plate; the latter extends distally with respect to the distal margins of the left and right intermediate lateral marginal plates, and bears a robust, distal triangular process. Other features of Paranacystis simoneae are: the presence of knobs on the proximal three-quarters of the lateral margins of the two proximal lateral marginal plates; the presence of two latero-distal pits, probably associated with the main orifice of the body; and a well-developed styloid process. Paranacystis simoneae extends both the geographical and the stratigraphical range of the genus, and strengthens the links between Malvinokaffric fossil faunas from the central and western parts of Gondwana in the Devonian.
Main article
Keywords: Paranacystis, Waboomberg Formation, Middle Devonian , Bokkeveld Group. South Africa.